African cutaneous histoplasmosis: two particular pediatric forms. - Ahogo, K.C.; Kanga, K.; Kouassi, K.A.; Sylvanus, K.; Allou, A.S. (European Journal of Pediatric Dermatology, 2018)
African cutaneous histoplasmosis is a rare mycosis. It usually occurs in patients immunecompromised by HIV. The occurrence of the disease in the immune-competent is rarely described and often present with papules. The clinical aspects actually are numerous and misleading. We report 2 cases of African histoplasmosis in immune-competent children. The first case occurred in an 11-year-old child as multiple subcutaneous nodules simulating lipomas and the second case presented as multiple ulcerated lesions of the face in a 13-year-old patient.